UPACARA SURAN JOMBOLEKA (STUDI BUDAYA MASYARAKAT KARANGPANDAN) - Prabowo, Agung (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret, 2014)
The purpose of this study is (1) Knowing the reason Suran Jomboleka still preserved by the community Karangpandan until now, (2) Knowing the public perception of Suran Jomboleka tradition, (3) Know the benefits of traditional values Ceremony Suran Karangpandan Jomboleka on people's lives.This study used a qualitative descriptive study design. Sample used is purposive sampling. While data collection techniques implemented by means of observation, interviews, and document analysis. To test the validity of the data the author uses triangulation of data sources and triangulation methods. Data analysis techniques in this study using a model of qualitative analysis and interactive analysis.Based on these results it can be concluded: (1) The ceremony Suran Jomboleka Talpitu Hamlet is based on belief or a strong impulse or because of feelings of fear of things that are not desirable (danger), so that people believe when carrying out the ceremony regularly every year, the village will be protected from all adverse events, and, if violated, will get a bala '. (2) Public perception of Suran Jomboleka ceremony, the authors classified into two categories, the first is the old group, this group still upholds the traditions or customs. The second is a young group, the response of this group to the ceremony Suran Jomboleka diverse, it is influenced by the level of education and the thickness of one's faith. This class of rational thinking, because of their higher levels of education, also established a devout prayers and other Islamic teachings. (3) Suran ceremony Jomboleka have values that can be useful in public life, among others. First, Suran Jomboleka ceremony is a form of gratitude for the blessings that have been bestowed by God. Secondly, Caution. Third, Advancing culture and art. Keywords : Suran Jomboleka, Cultural Ceremony